2018
DOI: 10.3389/fimmu.2018.02187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute and Chronic Exercise on Immunological Parameters in the Elderly Aged: Can Physical Activity Counteract the Effects of Aging?

Abstract: Immunosenescence is characterized by deterioration of the immune system caused by aging which induces changes to innate and adaptive immunity. Immunosenescence affects function and phenotype of immune cells, such as expression and function of receptors for immune cells which contributes to loss of immune function (chemotaxis, intracellular killing). Moreover, these alterations decrease the response to pathogens, which leads to several age-related diseases including cardiovascular disease, Alzheimer's disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
146
3
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(177 citation statements)
references
References 156 publications
4
146
3
15
Order By: Relevance
“…The extent of exercise-induced changes to the immune system in the elderly is quite diverse and depends on the type of physical activity as well as the volume and intensity of exercise. Future analyses will allow to understand the role which physical activity sustained throughout life plays on prevention of immunosenescence and lifestyle diseases [56].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of exercise-induced changes to the immune system in the elderly is quite diverse and depends on the type of physical activity as well as the volume and intensity of exercise. Future analyses will allow to understand the role which physical activity sustained throughout life plays on prevention of immunosenescence and lifestyle diseases [56].…”
Section: Discussionmentioning
confidence: 99%
“…Immunosenescence affects the function and phenotype of immune cells, such as the expression and function of receptors for immune cells, which contributes to a loss of the immune function (chemotaxis, intracellular killing). 8) Furthermore, these alterations decrease the response to pathogens, which leads to several age-related diseases, including cardiovascular disease, Alzheimerʼs disease, and diabetes in older individuals. 8) In addition, the risk of autoimmune disease and chronic infection increases with the aging of the immune system, which is characterized by a pro-inflammatory environment, ultimately leading to accelerated biological aging.…”
Section: Discussionmentioning
confidence: 99%
“…8) Furthermore, these alterations decrease the response to pathogens, which leads to several age-related diseases, including cardiovascular disease, Alzheimerʼs disease, and diabetes in older individuals. 8) In addition, the risk of autoimmune disease and chronic infection increases with the aging of the immune system, which is characterized by a pro-inflammatory environment, ultimately leading to accelerated biological aging. 8) The present study showed that the main cause of an increased CRP level on arrival among traumatized patients was infection, but this increased CRP level did not significantly affect the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphocytosis is caused by recruitment of NK, T, and B lymphocytes. 37,39 Results may suggest that the chronic effect of exercise was the most expressive stimulus in the induction of white blood cell increase in leukometry, which is fundamental in innate and acquired immune responses. The increase in leukometry was related to a plasma BDNF increase in trained diabetic animals, which corroborates with the study by Azoulay et al 40 Their results demonstrated that these factors have the ability of promoting chemotaxis and myeloproliferative increase and effect in animals through the interaction with CXCR4 receptors.…”
Section: Evaluation Of Hematological Parameters Leukometry and Leukocmentioning
confidence: 99%